PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL PROVINSI JAWA BARAT - Cindriyanti; Susy Hambani; Saepul Anwar (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
In building sustainable infrastructure and facilities, capital expenditure is an important factor that must be considered in addition to other expenditures. Regional revenues from PAD, DAU, and DAK can be used to improve public institution services and increase capital expenditure for economic growth. This study aims to analyze the influence of Regional Original Revenue, General Allocation Funds and Special Allocation Funds on Capital Expenditure of West Java Province in 2018-2022. This study uses a quantitative causality approach. The sampling method uses a saturated sampling technique. The results of this study show that Regional Original Revenue, General Allocation Fund and Special Allocation Fund simultaneously affect Capital Expenditure. Partially, Regional Original Revenue and General Allocation Fund have an effect on Capital Expenditure. Meanwhile, the Special Allocation Fund has no effect on Capital Expenditure.